PENGARUH PROFITABILITAS, LEVERAGE, AKTIVITAS DAN LIKUIDITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Damas Azrial akbar (Universitas Sains dan Teknologi Komputer, 2022)
Financial statements are very important for investors for making investment decisions. Financial ratios are very useful for predicting the stock price in an enterprise in the future. This is because financial ratios can be used as guidelines for investors regarding the past and future performance. The research data used is secondary data taken from the annual report on the Indonesia Stock Exchange (IDX) for 2018-2020. The population of this research is manufacture companies. Based on the purposive sampling method, the researches obtained 438 samples from 146 companies for 3 years, namely 2018-2020. This study uses panel data analysis techniques and SPPS. The results obtained show that the liquidity variable is a factor that influences the dependent variable in this study. Liquidity has a significant positive effect. And Leverage has a significant negative effect. Meanwhile, the factors that do not affect stock return are profitability and activity variables.